Local Wisdom Values of Self-Purity Tradition in Belahan Temple for The East Java Community - Moch. Zakki Mubarok; Niswatin; Nafisah, Durrotun (Program Studi Pendidikan IPS Unesa, 2025)
Indonesia is known as a country rich in local wisdom from various regions, inherited from ancestors who lived and endured to the present day. This study aims to explore the local wisdom values contained in the self-purification tradition at Belahan Temple in Wonosunyo Village, Gempol Subdistrict, Pasuruan Regency, East Java Province, and to analyze the relationship between humans and nature in the context of this local tradition. The research method employs a qualitative approach with data collection techniques through in-depth interviews, observations, and content analysis. The research findings reveal that the self-purification tradition is not only a series of rituals but also reflects cultural values passed down from generation to generation. The analysis of local wisdom values emerging from the self-purification tradition shows its connection to the concepts of sustainability, harmony, and respect for the natural environment. This research has significant implications for understanding the relationship between humans and nature, especially in the context of cultural sustainability and environmental preservation. The study provides new insights into how local traditions can serve as a means to enhance human awareness of the importance of preserving a harmonious relationship with nature.